Break Even Point Analysis As A Tool For Msmes Profit Planning In Sumber Jaya Sub - Distric, Bengkulu City - Halimatusyadiah Halimatusyadiah; Husaini Husaini (Universitas 45 Surabaya, 2023)
MSMEs in the Sumber Jaya sub-district generally micro-enterprises engaged in the fisheries sector, and a small proportion in the trade sector. In managing a business, generally MSMEs actors do not have knowledge of how to develop a business, increase sales and increase profits or profits, they only rely on intuition and technical knowledge from generation to generation. MSMEs actors only see that their businesses are running normally, but actually do not experience development. This can be seen from the quantity of sales and the number of workers that have not increased. Based on these conditions, there is a need for basic training related to profit planning from the businesses they manage. With the knowledge of profit planning, micro business actors in Sumber Jaya village are expected to develop their businesses.